Operational, interpersonal, discussional and ideational dimensions of classroom norms for dialogic practice in school mathematics. (7th June 2018) - Hofmann, Riikka; Ruthven, Kenneth
Abstract : While research suggests that interactive pedagogy drawing on students' ideas can improve learning outcomes, it has been found difficult to change mathematics classroom practice in this direction. The reasons for this difficulty remain poorly understood, hindering change at scale. This article focuses on the under‐researched normative aspect of such practice which shapes participants' actions and expectations. Drawing on theories of social practice and interaction, we define norms as recurrent and socially obligating patterns of, and rationales for, behaviour in a particular social practice. We then examine empirically what and how (new) norms associated with this type of pedagogy are manifest in classroom discursive activity by examining talk across 21 school mathematics lessons by 12 teachers implementing a dialogic intervention. While there is a clear distinction between surface norms and underlying rationales, and a consistent set of surface norms relating to classroom talk can be identified, deeper analysis finds norms to be multi‐dimensional. We illustrate how a surface norm, such as 'Respect others' ideas', can be enunciated in terms of multiple underlying rationales which we term operational, interpersonal, discussional and ideational. Our findings shed new light on why the dialogic intentions of such interventions are often realised in a superficial way. We further examine the ways in which teachers hold students and themselves accountable to the ideational dimension—the dimension that relates to taking students' ideas seriously in classroom dialogue.